2021
DOI: 10.3390/ma14174797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on the Dimensional Stability of Extruded Pure Aluminum

Abstract: High-performance extruded aluminum alloys with complex textures suffer significant dimension variation under environmental temperature fluctuations, dramatically decreasing the precision of navigation systems. This research mainly focuses on the effect of the texture of extruded pure aluminum on its dimensional stability after various annealing processes. The result reveals that a significant increment in the area fraction of recrystallized grains with <100> orientation and a decrement in the area fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…The reason for the inclusion of the Cu element is that part of the Cu element is dissolved in the phase precipitation process [ 34 ]. From Figure 4 c,d, the interplanar spacing of the (111) plane for the α-Al is 0.2357 nm, which is close to the value of 0.234 nm of the pure Al [ 39 ]. The reason for this difference may be the result of lattice distortion of the complex composition.…”
Section: Resultssupporting
confidence: 54%
“…The reason for the inclusion of the Cu element is that part of the Cu element is dissolved in the phase precipitation process [ 34 ]. From Figure 4 c,d, the interplanar spacing of the (111) plane for the α-Al is 0.2357 nm, which is close to the value of 0.234 nm of the pure Al [ 39 ]. The reason for this difference may be the result of lattice distortion of the complex composition.…”
Section: Resultssupporting
confidence: 54%
“…Fu et al studied the reasons for the reduction in the dimensional stability of high-performance extruded pure aluminum after annealing under thermal cycling. They found that the texture after annealing under thermal cycling rotated from parallel <111> to parallel <100> along the extrusion direction, and the change in grain direction led to the change in plane spacing, which further affected the dimensional stability of high performance extruded pure aluminum after annealing [ 15 ]. Dong et al studied the influence of quenching speed on the microstructure, residual stress, and dimensional stability of the Al–Cu–Mg–Si alloy.…”
Section: Introductionmentioning
confidence: 99%